2015
DOI: 10.1093/eurheartj/ehv337
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves peak oxygen consumption and haemodynamics in patients with severe pulmonary arterial hypertension and inoperable chronic thrombo-embolic pulmonary hypertension: a prospective, randomized, controlled trial

Abstract: AimsThe impact of exercise training on the right heart and pulmonary circulation has not yet been invasively assessed in patients with pulmonary hypertension (PH) and right heart failure. This prospective randomized controlled study investigates the effects of exercise training on peak VO2/kg, haemodynamics, and further clinically relevant parameters in PH patients.Methods and resultsEighty-seven patients with pulmonary arterial hypertension and inoperable chronic thrombo-embolic PH (54% female, 56 ± 15 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
221
3
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(253 citation statements)
references
References 38 publications
11
221
3
18
Order By: Relevance
“…The patient in this study had a 50 per cent reduction in his dyspnoea, going from 4 to 2, a situation that completely changes the outlook regarding the appearance of symptoms during the performance of activities of daily living. There were benefits in the functional classification of the WHO, starting in class III and ending in class II, which is similar to that found by Ehlken et al, 30 who in a clinical trial found in 3 weeks of training significant improvements in the functional class of 2.8±0.6 to 2.4±0.5; however, although in this and in Grunig's study 31 there was a decrease in the average classification score, it could not be established if they changed the grade from one stage to another, as it does in the case reported by us.…”
supporting
confidence: 88%
“…The patient in this study had a 50 per cent reduction in his dyspnoea, going from 4 to 2, a situation that completely changes the outlook regarding the appearance of symptoms during the performance of activities of daily living. There were benefits in the functional classification of the WHO, starting in class III and ending in class II, which is similar to that found by Ehlken et al, 30 who in a clinical trial found in 3 weeks of training significant improvements in the functional class of 2.8±0.6 to 2.4±0.5; however, although in this and in Grunig's study 31 there was a decrease in the average classification score, it could not be established if they changed the grade from one stage to another, as it does in the case reported by us.…”
supporting
confidence: 88%
“…Several small studies have evaluated exercise training as an adjunctive therapeutic strategy in patients with chronic pulmonary hypertension. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although most of these studies were small and not designed to address clinical end points, such as mortality or hospitalizations, related to pulmonary hypertension, they have demonstrated a variable degree of improvement in exercise tolerance and quality of life in response to training.Therefore, because of the uncertainty about the benefit of structured exercise training programs in patients with pulmonary hypertension, we performed this systematic review and meta-analysis to assess the efficacy and safety of structured exercise training regimens in patients with pulmonary hypertension. …”
mentioning
confidence: 99%
“…44 Future studies are needed to determine whether these favorable effects of exercise training can translate into a reduction in long-term major adverse clinical outcomes. 14,[17][18][19][20][21][22]27,29 and peak absolute oxygen uptake (mL/min) on pooled analysis of included studies (n=6, B). 14,[19][20][21]27 The mechanisms underlying improvement in exercise tolerance with exercise training among patients with pulmonary hypertension are not well understood.…”
mentioning
confidence: 99%
“…Moreover, a clinically important research question is whether these drugs would increase exercise capacity in the hypoxic environment also in patients with PAH/CTEPH or other respiratory diseases. Whether supplemental oxygen therapy in addition to current drugs would improve the capacity to perform daily activities or effectiveness of training in PAH/CTEPH patients with exercise-induced hypoxemia remains to be determined in future randomized trials (11). Further studies might investigate other potential therapeutic options, such as inhaled steroids, betamimetics, and other agents (6,54).…”
Section: Therapeutic Implications and Future Researchmentioning
confidence: 99%